2022
DOI: 10.1002/npr2.12229
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for readmission in schizophrenia treated with combined psychoeducation and standard therapy

Abstract: Background We conducted a historical cohort study of patients with schizophrenia to identify more robust risk factors at discharge that contribute to readmission within a year. Methods and Findings The subjects underwent brief psychoeducation during hospitalization. Multivariate analysis was conducted using factors selected in the univariate analysis. Using logistic regression analysis, the number of hospital admissions (P = .01) and Schedule for Assessment of Insight Japanese version score (P = .04) were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…Previous research also identified younger age [ 38 ], unmarried status [ 37 , 39 ], unemployment [ 37 , 40 ] and longer admission days [ 39 ] as factors associated with 1-year readmission. A Japanese study highlighted that a higher number of hospitalisations and higher scores on the Schizophrenia Cognition Rating Scale Japanese version (SCoRS-J), assessing cognitive functions in schizophrenia, were identified as risk factors for readmission [ 41 ]. Furthermore, it was highlighted that the risk of readmission in patients with severe mental disorders was increased by 25% for those treated with typical antipsychotics, compared to those who used atypical ones [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also identified younger age [ 38 ], unmarried status [ 37 , 39 ], unemployment [ 37 , 40 ] and longer admission days [ 39 ] as factors associated with 1-year readmission. A Japanese study highlighted that a higher number of hospitalisations and higher scores on the Schizophrenia Cognition Rating Scale Japanese version (SCoRS-J), assessing cognitive functions in schizophrenia, were identified as risk factors for readmission [ 41 ]. Furthermore, it was highlighted that the risk of readmission in patients with severe mental disorders was increased by 25% for those treated with typical antipsychotics, compared to those who used atypical ones [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…El abuso de sustancias se ha identificado como uno de los factores influyentes en las hospitalizaciones de pacientes con esquizofrenia (Rozin et al, 2019). Factores de riesgo demográficos como el estado civil, la edad, el género, las hospitalizaciones previas, la falta de apoyo familiar, apoyo social y el incumplimiento de la medicación, se han determinado como causas de reingreso de los pacientes con trastorno de esquizofrenia (Grudnikoff et al, 2019;Lorine et al, 2015;Sugisawa et al, 2022). En consecuencia, reducir el número de hospitalizaciones y de reingresos es de suma importancia para los servicios de psiquiatría en CyL.…”
Section: Hipótesisunclassified
“…El riesgo de consumir alcohol, tabaco y drogas es dos veces más común entre las personas con trastornos esquizofrénicos que en la población general (Thomsen et al, 2018). Se han identificado otros factores de riesgo relacionados con las hospitalizaciones previas (Grudnikoff et al, 2019), la raza, el estado civil, la edad, el género (Sugisawa et al, 2022), determinantes sociales como la falta de apoyo familiar, de relaciones sociales (Lorine et al, 2015), el acceso a la atención ambulatoria y el incumplimiento de la medicación (Portela et al, 2022).…”
Section: Hospitalizacionesunclassified
See 1 more Smart Citation